(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Due to their religious beliefs, Arabs had to take strict measures to ensure the writing, preservation, interpretation, and study of the text of the Qur’an, as well as the correct pronunciation and interpretation of the holy book of Muslims, in order to prevent its meaning from being corrupted. This task could only be accomplished successfully if there was a strict system of rules for the literary Arabic language.